Implementasi Metode Talaqqi dalam Pembelajaran Tahfidz Qur’an Siswa Halaqah Tahfidz di SDIT Baitul Hamdi Kota Padang - Sarianti, Yulia; Ikhlas, Al (Lembaga Yasin AlSys, 2024)
This study aims to determine the implementation of the talaqqi method in learning Qur'an tahfidz halaqah tahfidz students at SDIT Baitul Hamdi Padang City. This research uses qualitative methods with a case study approach. The data collection techniques used are interviews, observations and documentation studies. The source of the data was taken from ten informants through in-depth interviews. The informant is a teacher / ustadzah and student of halaqah tahfidz at SDIT Baitul Hamdi Kota Padang. All interview results were then analyzed thematically using Nvivo12 qualitative analysis software. Overall, the results of the analysis show that there are: first, in the implementation of the talaqqi method in learning Qur'an tahfidz halaqa tahfidz students there are three stages, namely planning; by preparing learning media, grouping students, making mutaba'ah books, and making student attendance lists, implementation; consisting of introduction, core and closing, evaluation; consists of midterm evaluation, and end-of-semester evaluation. Second, Factors supporting the implementation of the talaqqi method in learning Qur'an tahfidz are; The ability of teachers, cooperation between teachers and parents, using the same mushaf, then there is a tahfidz graduation. While the inhibiting factors are; Teachers do not have the ability to accumulate, children are often absent and short time. The results of this study can be used as evaluation material for teachers and as a determinant to choose the right method for the school in improving the quality and quantity of children's memorization.